Comparing Treatment with a Control Using Recovery of Inter-Block Information in Augmented Balance Incomplete Block Design - Mohamed, Badreldin A. (Gezira Journal of Engineering and Applied Sciences, 2018)
Many times, the experimenter wishes to compare treatments with a control, in incomplete block designs. To obtain greater precision for such comparisons, the control occurs more often in each block. The analysis of such designs using recovery of inter-block information is provided in this paper. Estimates of the weights for combining intra and inter-block estimates are also provided. Key words: Control, incomplete block designs, recovery of inter-block information, estimation of weights.